Author jdemeyer
Recipients eric.smith, jdemeyer, mark.dickinson, rhettinger, sir-sigurd, tim.peters
Date 2018-09-25.08:46:24
SpamBayes Score -1.0
Marked as misclassified Yes
Message-id <1537865184.74.0.545547206417.issue34751@psf.upfronthosting.co.za>
In-reply-to
Content
> j is even implies (j ^ -3) == -(j ^ 3)

This follows from what I posted before: if j is even, then j ^ 3 is odd, so we can apply the rule x ^ -2 = -x to x = j ^ 3:

(j ^ 3) ^ -2 = -(j ^ 3)

which implies

j ^ (3 ^ -2) = -(j ^ 3)

or equivalently

j ^ -3 = -(j ^ 3)
History
Date User Action Args
2018-09-25 08:46:24jdemeyersetrecipients: + jdemeyer, tim.peters, rhettinger, mark.dickinson, eric.smith, sir-sigurd
2018-09-25 08:46:24jdemeyersetmessageid: <1537865184.74.0.545547206417.issue34751@psf.upfronthosting.co.za>
2018-09-25 08:46:24jdemeyerlinkissue34751 messages
2018-09-25 08:46:24jdemeyercreate